Perceptions du changement climatique, impacts environnementaux et stratégies endogènes d’adaptation par les producteurs du Centre-nord du Burkina Faso - Pamalba Narcise Kabore; Bruno Barbier; Paulin Ouoba; André Kiema; Léopold Some; Amadé Ouedraogo (VertigO)
Climate change represents a major potential threat to the viability of rural households in sub-Saharan Africa who live mainly from the exploitation of natural resources. The purpose of this study is to analyze farmers’ perceptions of climate change, its environmental impacts, coping strategies and the relationships between them. Surveys were conducted through group discussions and an individual questionnaire administered to 300 households in north-central Burkina Faso. A Logit binary model identified factors that influence local perceptions of climate change and the choice of adaptation strategies. The study shows that farmers perceive a decrease in rainfall (76.7 %), a rise in temperatures (97 %) and strong winds (98.7 %). The determinant factors of this perception are education level of the household head, household size, belonging to a peasant organization and number of cattle. Land degradation mainly results in bare soils, reduced woody vegetation and low agricultural yields. The main adaptation strategies are the adoption of water and soil conservation techniques (WSCT), possession of manure pits, irrigation and the use of adapted varieties. The determining factors of this adaptation are the availability of picks and shovels, belonging to a peasant organization, training in agricultural technologies and access to credit. The adoption of an adaptation strategy by a farmer depends of his perception of climate change and its causes, its negative impacts on the environment and the means available to provide solutions.